Optimizing the Implementation of Child-Friendly Based School Development Plans in the Tropical Rain Forest Climate Area at Samarinda 9 State Senior High School - Kurnia Hastuti, Deni; Hanim, Zaenab; Aslindah, Andi; Kurniawan, Virdy (Educationist: Journal of Educational and Cultural Studies, 2023)
This study aims to describe: (1) optimizing child-based school development plan (RPS) in the humid forest climate in SMA Negeri 9 Samarinda, (2) optimizing the implementation of child-friendly RPS based on humid forest climate in SMA 9 Samarinda, and ( 3) supporting and inhibiting factors for the implementation of child-friendly based RPS optimization in humid forest climate in SMA Negeri 9 Samarinda This research was conducted in Samarinda 9 Public High School by using a qualitative approach with a case study method. The research subjects are child-friendly based school programs. The informants used were principals, teachers, students and parents. Data collection techniques (1) in-depth interviews, (2) observation, and (3) documentation. The collected data is examined for the validity of the data using triangulation of sources and techniques. The results showed that: (1) planning for child-friendly RPS based on humid forest climate in SMA Negeri 9 Samarinda has been carried out by planning a program involving all elements and compiling in RKAS, (2) implementing child-based based RPS optimization has been carried out fulfilling 6 indicators: (a) i.e. non-violence declaration program policies (b) teaching and learning activities carried out contextually with the environment (c) infrastructure is sought to be comfortable and safe for students, (d) student participation is involved in school activities, (e) active parent participation accompany their children's learning at home, (f) participation with the business world in cooperation with PT. Garuda Sinar Perkasa; (3) one of the supporting factors of the program is the cooperation of all school residents, and the inhibiting factors are flooding and coordination technical obstacles. From the results of the study, it can be concluded that the optimization of the implementation of child-friendly RPS based on humid forest climate in SMA Negeri 9 Samarinda has been carried out optimally despite several obstacles.